Complement metabolism in man: hypercatabolism of the fourth (C4) and third (C3) components in patients with renal allograft rejection and hereditary angioedema (HAE) - Carpenter, Charles B. (1969)
Highly purified and radioiodinated human C4 and (or) C3 were administered to patients with renal allografts in rejection, with hereditary angioedema (HAE), with chronic glomerulonephritis, and to control subjects. The latter group included normal individuals, anephric patients before transplantation, and stable renal allograft recipients. The catabolic rates of these complement proteins were determined by analysis of the disappearance of plasma protein-bound radioactivity (k(m)), and by direct measurement of urinary excretion of radioactivity (k(u)). The correlation coefficient between these two methods was 0.96. The mean ±2 SD for catabolic rates in the control subjects was 0.9-2.7% plasma pool/hr for C4 and 0.9-2.0% plasma pool/hr for C3. Patients experiencing renal allograft rejection had unstable levels of C4 and C3, and exhibited moderate hypercatabolism of both proteins. One patient with chronic glomerulonephritis had hypercatabolism of C4 and C3 in the presence of stable normal serum levels. In patients with HAE who had extremely low levels of C4, catabolic rates for C4 were markedly elevated (3.7, 5.8, 7.0 and 8.8%/hr). Analysis of plasma curves in HAE revealed a three component disappearance curve instead of the two component curve in control subjects receiving the same preparation. Even though C3 levels were normal, moderate hypercatabolism of C3 was also present in HAE (2.6, 2.8, 2.8, and 3.2% of pool/hr). The marked hypercatabolism of C4 in HAE constitutes the first direct evidence for the in vivo destruction by uninhibited C1 esterase of its natural substrate C4. The moderate hypercatabolism of C3 is consistent with the in vivo formation of C3-convertase.